Enhancing Performance Of WLAN At KPTM Batu Pahat Using Channel Assignment - Fatahurahman, Noor Atiqah (UTeM, 2016)
Nowadays, Wireless Local Area Network (WLAN) has been growing rapidly in the world, especially in business and education institutions. There are much type of wireless technology on the market today such as Institute of Electrical and Electronics Engineer (IEEE) 802.11a, b, g, and n series. WLAN generally consist of a central point connection called an Access Point (AP). It is the same function as hubs or switches in a star topology-based, traditional wired networks in the local area network. The Access Point (AP) can transmit data between different node of the wireless local area network and it serves as the only connection between wireless LAN and wired LAN. The rapid development of WLAN campus, it is easier for the lecturers and students gain access to targeted information anytime and anywhere. WLAN is also caused the lecturers and the students depend on WLAN to access the information anywhere. Besides that, WLAN provide great freedom and enables users to communicate and facilitate the users to communicate without special sitting at the computer. WLAN has become a very important part in university and campus life for student and lecturers. This project wants to identify the issue arise from the use of WLAN from the perspective of user and particularly from the perspective of student and lecture. There are many issues in the implementation of WLAN in Kolej Poly-Tech MARA (KPTM) Batu Pahat, which is the coverage of WLAN limited to access, slow connection, sometimes it can be shared sometimes not and the number of APs do not support the number of existing users. This project also want to investigate about the coverage of WLAN, the channels used and channel overlapping in the Kolej Poly-Tech MARA (KPTM) Batu Pahat. In addition, this thesis aims to improve the performance of wireless networks in the Kolej Poly-Tech MARA (KPTM) Batu Pahat.